Inflammatory response in Colombian children with severe protein-energymalnutrition before and after nutritional intervention. (2010)
ABSTRACT: Aim: To evaluate the changes in C-reactive protein and pro-inflammatory cytokines in severely malnourished children, before nutritional intervention and at the moment of restoring appetite. Methodology: To assess changes in inflammatory mediators, 20 severely malnourished children under 5 years of age, 10 with kwashiorkor and 10 with marasmus were studied. Hemoglobin, total serum proteins, albumin, ferritin, transferrin, ceruloplasmin, C-reactive protein and pro-inflammatory cytokines (IL-8, IL-1β, IL6, IL-10, TNF-α, and IL-12p70) were determined. Results: Upon hospital admission, the mean values of C-reactive protein in kwashiorkor and marasmus patients (16.3±19.0mg/L and 23.1±27.9 mg/l, respectively) indicated an inflammatory response process with no difference between both groups (p=1.0). Total protein, albumin, transferrin and ceruloplasmin in children with kwashiorkor were significantly lower than in marasmic children (p=0.003, p=0.007, p=0.035, p=0.007, respectively). All cytokines, except IL-12p70, showed significantly higher concentrations in kwashiorkor than in marasmic children. After the stabilization phase, concentrations of C-reactive protein decreased significantly in both groups and albumin increased to normal values, but cytokines remained high. Conclusion: These results show that malnourished children are able to synthesize C-reactive protein in response to an infectious process. Additionally, higher levels of pro-inflammatory cytokines and depletion of albumin in children with kwashiorkor suggest that these inflammatory mediators could be critical biomarkers during clinical phases of kwashiorkor.